Electronic structure of a hydrogenated gallium nitride nanoparticle - Lavarda, Francisco Carlos [UNESP]; de Souza Schiaber, Ziani [UNESP]; de Conti Dias Aguiar, Leonardo [UNESP]; Oliveira, Eliezer Fernando [UNESP]; Gonçalves Leite, Douglas Marcel; Camilo, Alexandre [UNESP]; Dias da Silva, José Humberto [UNESP] (Wiley, 2015)
This paper investigates the geometrical, electronic, and optical properties of a Ga24N24H46 nanoparticle using Density Functional Theory (DFT). The results show that this nanoparticle maintains geometrical parameters very similar to those of the GaN crystal, although it was noticed that the bond length along the direction [0001] of the Ga24N24H46 nanoparticle is smaller than those of the base of the tetrahedron, which is the opposite of what occurs in the crystal. The bandgap of the passivated nanoparticle calculated with DFT is greater than that of the crystal, while an estimate for the hydrogen-free Ga24N24 structure shows a much lower bandgap, in accordance with the literature. The simulation of the optical absorption spectra via Time-Dependent DFT allowed the association of the spatial shape of electronic orbitals with particular transition energies. The highest occupied (HOMO) and lowest unoccupied (LUMO) electronic levels are located on the (0001) and (000-1) surfaces of the particle, respectively, showing that the passivation of GaN nanoparticles should maintain its known photocatalytic activity, and that transition probability between those surface states is relatively low as compared to the HOMO-4 and LUMO transitions at 4.16eV. Results are compared with the available experimental data.
Keywords: Density functional theory; Electronic structure; GaN; Hydrogenation; Nanoparticles